2008
DOI: 10.1152/jn.01205.2007
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Intrinsic Membrane Properties, and Rotation-Evoked Responses of Trochlear Motoneurons in the Turtle

Abstract: Jones MS, Ariel M. Morphology, intrinsic membrane properties, and rotation-evoked responses of trochlear motoneurons in the turtle. J Neurophysiol 99: 1187-1200, 2008. First published December 26, 2007 doi:10.1152/jn.01205.2007. Intrinsic properties and rotationevoked responses of trochlear motoneurons were investigated in the turtle using an in vitro preparation consisting of the brain stem with attached temporal bones that retain functional semicircular canals. Motoneurons were divided into two classes base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Threshold currents, ranging from 5 to 25μA, are also within physiological range used for other studies, and the frequency, 91 Hz (Figs. ), which maximally activates fibers, aligns with those known for neurons that would communicate with trochlear motoneurons (Jones and Ariel, , ).…”
Section: Discussionsupporting
confidence: 78%
“…Threshold currents, ranging from 5 to 25μA, are also within physiological range used for other studies, and the frequency, 91 Hz (Figs. ), which maximally activates fibers, aligns with those known for neurons that would communicate with trochlear motoneurons (Jones and Ariel, , ).…”
Section: Discussionsupporting
confidence: 78%
“…The size principle dictates the order of recruitment, small Mns being recruited before large ones, and the crucial property determining systematic differences in recruitment is the input resistance. In trochlear Mns of the turtle, it has been reported that spiking in Mns of higher input resistance is recruited earlier (Jones and Ariel 2008). In oculomotor nucleus Mns of mammals (Nieto-Gonzalez et al 2007), we have found a poorly fitted linear regression between cell size and input resistance and a weak relationship between input resistance and I-F gain.…”
Section: Muscarinic Control Of the Oculomotor Nucleus Mns: Functionalmentioning
confidence: 48%
“…Second, this preparation uses the turtle's adaptive ability to lower its metabolism even further to survive long dives and a dormant state in water under frozen ponds for many winter months. Recordings from a variety of turtle brain stem regions have demonstrated the very low tonic synaptic and spike activity in this in vitro preparation (Fan et al , 1997Jones and Ariel 2008;Rosenberg and Ariel 1990). Responses in mammalian tissue are more active, even in vitro, so have exhibit more depolarized neuronal membranes on which inhibition can often be measured as a hyperpolarization (Cohen and Yarom 2000a).…”
Section: Responses To Io Stimulation Are Oriented Sagittally In Thementioning
confidence: 94%